2021
DOI: 10.1007/s00394-021-02715-9
|View full text |Cite
|
Sign up to set email alerts
|

Dairy intake and long-term body weight status in German children and adolescents: results from the DONALD study

Abstract: Purpose To analyse the association between intake of total dairy (TD) and types of dairy [liquid dairy (LD), solid dairy (SD), low-fat dairy (LFD), high-fat dairy (HFD), high sugar dairy (HSD), low-sugar dairy (LSD), not fermented dairy (NFD), as well as fermented dairy (FD)] and long-term changes in body weight status and composition among children and adolescents in Germany. Methods In total, 9999 3-day dietary records collected between 1985 and 2019 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
1
1
Order By: Relevance
“…High levels of adipose tissue were assumed to result in the development of insulin resistance (52) . In a previous study based on our sample, higher TD intake led to a more favourable body composition in the long term; however, higher intake of low-fat dairy showed no association (23) . However, our sample is characterised by a rather low BMI compared with the general population in Germany (53,54) .…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…High levels of adipose tissue were assumed to result in the development of insulin resistance (52) . In a previous study based on our sample, higher TD intake led to a more favourable body composition in the long term; however, higher intake of low-fat dairy showed no association (23) . However, our sample is characterised by a rather low BMI compared with the general population in Germany (53,54) .…”
Section: Discussioncontrasting
confidence: 65%
“…A finer subdivision would have led to very low intake quantities. The underlying classification has already been used in our previous publications ( 22 , 23 ) and allows an overall interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, several systematic reviews and meta-analyses in the paediatric population have demonstrated inconsistent and conflicting results [ 4 , 5 , 6 , 7 , 8 , 9 ]. The most recently published German longitudinal study with a median follow-up of 9 years in children demonstrated that the consumption of all types of dairy products was associated with significant increases in Body Mass Index (BMI) (although small) as well as in fat mass and lean mass [ 10 ]. The findings of the most recently conducted meta-analyses [ 9 ] revealed controversial findings depending on the study design.…”
Section: Introductionmentioning
confidence: 99%